Lessons Learned From Presumptive Condition Lists in Veteran Compensation Systems - Amy L. Hall; Paul A. Demers; Linda VanTil; Mary Beth MacLean; Maria E. Dalton; Trish Batchelor; Lesley Rushton; Tim R. Driscoll (Frontiers Media S.A., 2022)
Presumptive condition lists formally accept connections between military factors and veteran health conditions. An environmental scan of such lists and their evidentiary basis was conducted across four veterans' administrations to inform other administrations considering the development of such lists. Information on included conditions, qualifying military factors, and scientific processes was obtained through targeted internet searches and correspondence with veterans' administrations. The content of presumptive condition lists across jurisdictions varied by conditions included, as well as military eligibility requirements (e.g., service in particular conflict, context, or time period). Scientific review processes to develop lists also varied across jurisdictions. Findings indicate that evidence and experience may be leveraged across compensation systems (veteran and civilian). Ongoing research to understand links between military exposures and veteran health is recommended.